Hubungan Kreativitas Guru PAI dalam Mengintegrasikan Nilai-Nilai Islam dengan Kompetens Sosial dan Spiritual Siswa - Erico Zurisar; Parlaungan Lubis; Sulaiman Tamba (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to examine the relationship between PAI teachers' creativity in integrating Islamic values and students' social and spiritual competencies. A quantitative research method was employed, as the collected data were analyzed using statistical techniques. The findings indicate that the creativity level of PAI teachers falls into the “very good” category, with an average score of 4.35. The highest indicator appears in the use of digital media and varied learning methods, such as Islamic video materials, interactive presentations, and the Quizizz platform. Meanwhile, the lowest indicator is found in innovative learning evaluation, suggesting that project-based authentic assessment still requires improvement. These results show that teachers' creativity has a positive relationship with students' social and spiritual competence development.